The Effect of Return On Equity, Debt To Equity Ratio And Current Ratio On Stock Returns With Inflation As A Moderating Variable In The Property & Real Estate Sector For The Period 2020-2022 - Fienda Putri; Heni Safitri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to determine whether there is a relationship between return on equity, debt to equity, and the current ratio of stock returns with inflation as a moderating variable. With a positive data collection strategy and a sample size of 70 companies in the property and real estate sector listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The statistical methods used in the analysis include: SEMP-PLS test, inner model test, and hypothesis test. Which shows the results that the variables ROE, DER, and CR have a negative and significant effect on stock returns, while the inflation variable cannot influence ROE, DER, and CR on stock returns in the property and real estate sector for the 2020-2023 period.